Is ‘Herding’ Peculiar to Certain Stocks? A Perspective from the Turkish Stock Market - İrem Çetinkaya; Mustafa Yildirim (Selçuk Üniversitesi Sosyal Bilimler Enstitüsü Dergisi)
We test the existence of daily/weekly herding behavior in the Turkish stock market between June 2013 and October 2020 on the stocks that remained listed on the benchmark stock index over the analysis period. Rather than performing the test on a set of stocks belonging to firms with different characteristics as in the literature, we conduct it on subsets of stocks we form based on foreign ownership ratio, firm size (measured by total assets), and prominent financial indicators (price-to-earnings and market-to-book ratios). Our analysis provides no evidence of herding behavior but yields important insights. Specifically, it demonstrates that financial indicators have no bearing on herding behavior, but investor type and firm size may. A slight indication of herding tendency emerges in stocks with a relatively higher investment from local investors but disappears in those with a comparatively higher investment from foreign investors. This finding suggests a potential market knowledge disparity between local and foreign investors, with the less expert being the local group. Moreover, a faint sign of herding tendency also appears in stocks that belong to small firms, possibly due to a heightened uncertainty inherent in such stocks.